2019
DOI: 10.1039/c8fo02376j
|View full text |Cite
|
Sign up to set email alerts
|

Lactulose synergizes with CpG-ODN to modulate epithelial and immune cells cross talk

Abstract: Apart from being a prebiotic and laxative, lactulose has direct immunomodulatory effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Previous studies using this well-established in vitro IEC/PBMC co-culture model reported regulatory-type Th1 responses upon exposure to NDO in association with bacterial DNA or synthetic CpG oligodeoxynucleotides, known to be TLR9 ligands. The immunomodulatory effects observed upon exposure to NDO and CpG in the IEC/PBMC model could support mucosal immune development and were shown to be mediated by epithelial-derived galectin-9, which was found to be a key mediator contributing to the effects observed in vitro [29][30][31]34,35]. These studies also showed that the immunomodulatory properties of CpG and NDO occurred only when the PBMC underlying the IEC were activated, mimicking inflammatory conditions [29].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Previous studies using this well-established in vitro IEC/PBMC co-culture model reported regulatory-type Th1 responses upon exposure to NDO in association with bacterial DNA or synthetic CpG oligodeoxynucleotides, known to be TLR9 ligands. The immunomodulatory effects observed upon exposure to NDO and CpG in the IEC/PBMC model could support mucosal immune development and were shown to be mediated by epithelial-derived galectin-9, which was found to be a key mediator contributing to the effects observed in vitro [29][30][31]34,35]. These studies also showed that the immunomodulatory properties of CpG and NDO occurred only when the PBMC underlying the IEC were activated, mimicking inflammatory conditions [29].…”
Section: Introductionmentioning
confidence: 74%
“…Within the DP2 fraction, various NDO structures have been characterized also including lactose residues [14]. Previous studies did not observe immunomodulatory effects upon exposure to lactose in the IEC/PBMC co-culture model [35]. However, due to the presence of lactose and the inability to separate this from other possible active NDO within the DP2 fraction, this study focused on analyzing GOS fractions with size of DP3 and longer fractions, namely DP4-7, DP3-7, and DP3-5 fractions, which were isolated by size-exclusion chromatography.…”
Section: Discussionmentioning
confidence: 99%
“…These differences could not be ascribed to differences in endotoxin contaminations in enzymatic or bacterial produced HMOS (presented in Table 1). The endotoxin contamination level of all used HMOS is low and not in a range to expect to significantly contribute to the immunological responses [33,65]. In the presence of CpG, enzymatic 2 FL further enhanced regulatory and Th1 type cytokine release from PBMCs and galectin-9 secretion from IEC, while also diminishing Th2 cell development.…”
Section: Discussionmentioning
confidence: 99%
“…However, this was not seen in rats receiving longer-sized fructo-oligosaccharides, suggesting that shorter NDO might be absorbed by enterocytes and thereby be able to promote immunomodulation as opposed to longer DP-sized NDO. Similar to the rat study, also a 9:1 mixture of short chain and long chain FOS as well as lactulose enhanced IFNg and IL-10 secretion on top of the effect of CpG in a similar co-culture model used to study GOS DP [85,86]. All these studies suggest that NDO like GOS/lcFOS, GOS or FOS/lcFOS may generate direct immunomodulatory effects mainly via interaction of their short-chain NDO with epithelial and/or immune cells.…”
Section: Ndo As Immunomodulatory Agentssupporting
confidence: 69%